Defendants negligence causing nervous shock or psychiatric injury to plaintiff/claimant: a critical appraisal - Shair Mohamad, Mohd Akram; Sardar Baig, Farheen Baig (International Organization Center of Academic Research (OCERINT) Publishing, 2017)
In the common law jurisdictions including Malaysia, the tort of negligence is based on the existence of a duty of care owed by the defendant to the plaintiff/claimant. The law has developed over time to include many instances where duty of care exists. Psychiatric injury is an aspect of negligence concerned with mental harm which has been caused through the negligent act of another. The essential question to be asked is the degree of proximity which is required when a person has suffered psychiatric damage as a result of the defendant’s negligent act. Initially the plaintiff could only succeed if he was also within the range of physical impact, i.e. only the ‘primary’ victim could sue. Later liability was extended to secondary victim. The appropriate test became foreseeability of the shock, but the problem is when shock is foreseeable? It is suggested the court in fact created ‘sub-rules’ or guidelines which indicated the kind of cases where proximity in the legal sense would exist. In Alcock v Chief Constable of South Yorkshire [1991] WLR 1057, the House of Lords appears to have adopted a compromise position whereby the test is one of ‘foresight’, but one where foresight has a coded meaning. So where the plaintiff has suffered psychiatric damage the test of proximity which is required to establish a duty of care is ‘foresight’ as determined in the light of the relevant guidelines, as to whether victim is the primary victim. The paper aims to give a critical appraisal of the unsatisfactory state of the law particularly in the case of secondary victim, suggesting reform in the light of many criticisms by leading authorities.